Assessing the Socioeconomic Determinants of Malaria Prevalence Among Students in Anyigba - Jamiu Adeniyi Yusuf; Dauda Musa Segun; Olalere Victoria Mayowa (CV Media Inti Teknologi, 2025)
Background: Malaria remains a major public health concern in Nigeria, with university students in endemic areas particularly vulnerable due to varying socioeconomic conditions. This study investigates the influence of socioeconomic factors on malaria prevalence among students of Kogi State University, Anyigba, Nigeria.Aims: The study aimed at assessing the socioeconomic determinants of malaria prevalence among students in Anyigba, Kogi State. To also examine the relationship between students' socioeconomic status and malaria incidence. To identify key environmental and behavioral factors contributing to malaria exposure, and to recommend policy and health interventions tailored to student populations in malaria-endemic areas.Methods: A cross-sectional descriptive design was adopted. Stratified random sampling was used to select participants across variables such as age, gender, income, and housing types. Data were collected through structured questionnaires and analyzed using logistic regression to determine significant predictors of malaria prevalence.Results: The findings revealed a high malaria prevalence among low-income students and those living in shared accommodations. Key determinants of malaria incidence included low income, poor housing conditions, and limited access to healthcare services. Notably, students with poor access to healthcare had a malaria prevalence of 68%, compared to 33% among those with better access.Conclusion: Socioeconomic factors significantly influence malaria prevalence in the student population. Financial constraints, inadequate housing, and poor healthcare access increase vulnerability to infection. An integrated malaria control approach is recommended, including university-led awareness campaigns, improved sanitation in student accommodations, and enhanced collaboration with local healthcare providers.